Breast Implant–Associated Anaplastic Large Cell Lymphoma: A Systematic Review. Issue 3 (March 2015) - Gidengil, Courtney A.; Predmore, Zachary; Mattke, Soeren; van Busum, Kristin; Kim, Benjamin
Abstract : Background: There is substantial evidence that a type of anaplastic large cell lymphoma (ALCL) is associated with breast implants. However, the course in patients with breast implants seems to be unusually benign compared with other systemic ALCL. The purpose of this study was to identify and analyze recently published cases of breast implant–associated ALCL, with an emphasis on diagnosis, staging, treatment, and outcomes. Methods: The authors conducted a systematic literature review of reported cases of ALCL in patients with breast implants. Publications were identified with a search algorithm and forward searches. Case-based data were abstracted independently and reconciled by multiple investigators. Results: Of 248 identified articles, only 102 were relevant to breast implant–associated ALCL, and 27 were included in this study. Fifty-four cases of ALCL in patients with breast implants were identified. Detailed clinical information was lacking in many cases. Most presented with a seroma (76 percent), and approximately half were associated with the capsule (48 percent). Most presented as stage IE (61 percent). All but one case were ALK-negative. Most received chemotherapy (57 percent) and radiation therapy (48 percent), and 11 percent received stem cell transplants. Approximately one-quarter recurred, and 9 percent died. Conclusions: Since the publication of guidance related to breast implant–associated ALCL in 2010, a number of cases have been reported. Despite the typically benign course, many of the cases have been treated with radiation therapy and/or chemotherapy. Increasing awareness of this disease entity among clinicians would be helpful, along with standardizing an approach to diagnosis, staging, and treatment. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, V. Abstract : Supplemental Digital Content is available in the text.